Tangeretin attenuates lipopolysaccharide-induced acute lung injury through Notch signaling pathway via suppressing Th17 cell response in mice. (January 2020) - Li, Mengqin; Zhao, Yan; Qi, Di; He, Jing; Wang, Daoxin
Abstract: Tangeretin, a polymethoxylated flavonoid is abundant in citrus fruits, which has been reported to inhibit inflammation by inhibiting NF-κB activation and proinflammatory cytokines. Notch blockage inhibits Th17 cells response that are involved in the development of acute lung injury (ALI). This study investigated the protective effects of tangeretin on LPS-induced ALI in mice. Male C57BL/6 mice were treated with phosphate-buffered saline (PBS), lipopolysaccharide (LPS), LPS and tangeretin, or LPS and N-[N-(3, 5-difluorophenacetyl)-l-alanyl]-S-phenylglycine t-butyl ester (DAPT, a Notch signaling inhibitor), which were harvested at 48 h after challenged by LPS. CD4 + T cells were treated with tangeretin or DAPT and harvested after 72 h. Tangeretin notably attenuated pathological changes and decreased the wet to dry weight ratio of the mouse lungs. The total cell and neutrophil counts, tumor necrosis factor (TNF)-α in bronchoalveolar lavage fluid (BALF), myeloperoxidase activity of lung tissue were markedly reduced by tangeretin. The percentage of CD4+IL-17 + T cells in the lungs and the concentration of interleukin (IL)-17 and IL-22 in BALF were significantly down-regulated by tangeretin. As with the positive control (DAPT), tangeretin inhibited the activity of the Notch signaling pathway accompanied with the down-regulation of acid-related orphan receptor gamma t and IL-23 receptor expression. This study demonstrated that tangeretin protects against LPS-induced ALI by suppressing Th17 response at least partially, through a Notch-dependent mechanism. Highlights: Tangeretin attenuated LPS-induced ALI by ameliorating inflammation in mouse lungs. Tangeretin attenuated infiltration and activation of neutrophil via suppressing Th17 response in mouse lungs. Tangeretin suppressed Th17 response via Notch signaling pathway. Tangeretin decreased RORγt and IL-23 R expression at both the transcriptional and translational levels.